Peran Pasar Modal Syariah dalam Mendorong Laju Pertumbuhan Ekonomi di Indonesia - Prasanti, Asri Raihana; Zahrotunnisa, Elisda; Wahyu, Muhammad Fadli (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2022)
Investment is a part of country’s income. With the islamic capital market which facilitate investment activities, it will boost the economic growth. This study aims to see how big the influence of the role of the Islamic capital market to encourage the rate of economic growth in Indonesia. Narrative review is used in this article in analysing literatures that have been gathered that is related to the theme in this article. The development of Islamic capital market in Indonesia continues to grow from year to year. The institution become the driving force of economic growth in Indonesia from investment channel. The increase of investment then affect to the development of Islamic capital market. This indicates that from time to time, Islamic capital market will increase its major role in increasing economic growth in Indonesia.